Participatory scenario planning for sustainable irrigated agriculture when actors seldom communicate: an experiment in Morocco. Issue 6 (2nd November 2018) - Faysse, Nicolas; Sellika, Issam Eddine; Rinaudo, Jean-Daniel; Errahj, Mostafa
ABSTRACT: In Morocco, agricultural activities based on groundwater use increasingly face risks of aquifer overdraft and market saturation. However, farmers and public organizations responsible for agriculture and water resources rarely communicate to identify how these risks could be overcome. A participatory scenario-planning process was organized in a small region to identify a pathway towards agricultural activities that are sustainable in terms of groundwater resource use and profitability. Actors jointly determined this pathway thanks to the organization of preparatory workshops held separately with each actor before they met together, and the progressive integration of agriculture development and groundwater use in scenario design.